Immune Response-Dependent Assembly of IMP Dehydrogenase Filaments - Calise, S. John; Abboud, Georges; Kasahara, Hideko; Morel, Laurence; Chan, Edward K. L. (Frontiers in Immunology, 2018)
Inosine monophosphate dehydrogenase (IMPDH) catalyzes the conversion of IMP to xanthosine monophosphate, the rate-limiting step in de novo guanosine monophosphate (GMP) synthesis. In cultured cells, IMPDH polymerizes into micron-scale filamentous structures when GMP synthesis is inhibited by depletion of purine precursors or by various drugs, including mycophenolic acid, ribavirin, and methotrexate. IMPDH filaments also spontaneously form in undifferentiated mouse embryonic stem cells and induced pluripotent stem cells, hinting they might function in various highly proliferative cell types. Therefore, we investigated IMPDH filament formation in human and murine T cells, which rely heavily on de novo guanine nucleotide synthesis to rapidly proliferate in response to antigenic challenge. We discovered extensive in vivo IMPDH filament formation in mature T cells, B cells, and proliferating germinal center cells of normal, adult B6 mice. Both cortical and medullary thymocytes in young and old mice also showed considerable assembly of IMPDH filaments. We then stimulated primary human peripheral blood mononuclear cells ex vivo with T cell mitogens phytohemagglutinin (PHA), concanavalin A (ConA), or antibodies to CD3 and CD28 for 72 h. We detected IMPDH filaments in 40-60% of T cells after activation compared to 0-10% of unstimulated T cells. Staining of activated T cells for the proliferation marker Ki-67 also showed an association between IMPDH filament formation and proliferation. Additionally, we transferred ovalbumin-specific CD4+ T cells from B6.OT-II mice into B6.Ly5a recipient mice, challenged these mice with ovalbumin, and harvested spleens 6 days later. In these spleens, we identified abundant IMPDH filaments in transferred T cells by immunofluorescence, indicating that IMPDH also polymerizes during in vivo antigen-specific T cell activation. Overall, our data indicate that IMPDH filament formation is a novel aspect of T cell activation and proliferation, and that filaments might be useful morphological markers for T cell activation. The data also suggest that in vivo IMPDH filament formation could be occurring in a variety of proliferating cell types throughout the body. We propose that T cell activation will be a valuable model for future experiments probing the molecular mechanisms that drive IMPDH polymerization, as well as how IMPDH filament formation affects cell function.